FUNGSI TRADISI BEDAH BLUMBANG DALAM PELESTARIAN AREA KONSERVASI AIR DI KAKI GUNUNG UNGARAN KABUPATEN SEMARANG - Wiyatasari, Reny; Lathifah, Afidatul (Studi Budaya Nusantara, 2019)
Abstract Bedah Blumbang carried out in Dusun Gintungan, Semarang District that near from Ungaran Mountain is a series of merti desa ceremonies or often known as the cleaning village tradition. This article discusses how the role of the bedah blumbang in the practice of water resources conservation at the Ungaran Mountain and the meaning of the tradition in the Gintungan Hamlet community. The practice of bedah blumbang has undergone a variety of changes and improvisations, ranging from procedures, completeness of ceremonies, to community involvement. Not only the Gintungan?s community is involved, but also the stakeholders at the government level. Bedah blumbang is also one of the tourist attractions in Dusun Gintungan . The abundance of water in Dusun Gintungan has also not been well managed, people thinking that water is a resource that will not run out so people tend to use it without limits. However, the myths that develop in the community around the source of the spring become the control of the community in utilizing the natural resources around them, especially water resources. Bedah blumbang functions as a guardian of tradition, guards of harmony between residents, a tour event, and as a reminder of their ancestors. The process of environmental conservation indirectly occurs when remembering myths about ancestors, thus residents continue to maintain the sustainability of blumbang which is a source of water for residents of Gintungan Hamlet and its surroundings. This research is qualitative research with data collection techniques in the form of in-depth interviews and participant observation. In-depth interviews and observations are intended to obtain primary data.